Sonochemical synthesis of fluorescent 1, 4-disubstituted triazoles using l-phenylalanine as an accelerator ligand in aqueous media. Issue 18 (2nd May 2019) - Jain, Yachana; Kumari, Mitlesh; Gupta, Ragini
Graphical abstract: Highlights: Ultrasound assisted synthesis of 1, 4-disubstituted-1, 2, 3-triazoles at 40 °C in aqueous media. This protocol exploits biocompatible, easily availablel -phenylalanine as a promotor ligand. Recyclability ofl -Phenylalanine/Cu(I) system up to 5 cycles. High product yield (up to 97%) in lesser reaction time (80 min). Gram scale synthesis. Abstract: A green sonochemical protocol usingl -phenylalanine as a water soluble promotor ligand has been developed for the regioselective synthesis of fluorogenic 1, 4-disubstituted triazoles (3a-o) via well-known click reaction at 40 °C.l -Phenylalanine is a biocompatible, economical, commercially available and non-toxic ligand which not only serves to stabilize Cu(I) oxidation state but also prevents its disproportion to enhances and modulate the rate of reaction. The designed catalytic system exhibits broad substrate compatibility and can be recycled up to 5 cycles without appreciable loss in the yield of desired product. Gram scale synthesis was successfully accomplished with 92% yield.